KOMPETENSI KOMUNIKASI CALON SDM PUBLIC RELATIONS - A. Rahman (Jurnal Visi Komunikasi, 2015)
Public Relations as human resources hould have the competence that has a sale value in the labor market. One such communication competence is knowledge of communication, communication skills, motivation communication and managing interaction. Study of communication competence among students obtained the result that public Relations Group one are not sufficiently competent in listening, conveying the idea of writing, controlling the communication situation, a way of communicating with new people, motivating others through communication, understanding others, tense in communicating, and controlling communications the ability is low.While the communication competence is likely to adequately classified by phone: the ability, oral communication, communication skills via e-mail, the ability to pay attention to non-verbal message the speaker, motivational communication not only in its favor, and adaptability to different communication situations.Group two have a adequate communication of knowledge, skills, motivation and ability managing interaction. Some of the things he view is still lacking is the ability to communicate with new people who know, the ability to motivate others through communication (persuasive abilities), the attraction and motivation to communication. Public Relations as human resources hould have the competence that has a sale value in the labor market. One such communication competence is knowledge of communication, communication skills, motivation communication and managing interaction. Study of communication competence among students obtained the result that public Relations Group one are not sufficiently competent in listening, conveying the idea of writing, controlling the communication situation, a way of communicating with new people, motivating others through communication, understanding others, tense in communicating, and controlling communications the ability is low.While the communication competence is likely to adequately classified by phone: the ability, oral communication, communication skills via e-mail, the ability to pay attention to non-verbal message the speaker, motivational communication not only in its favor, and adaptability to different communication situations.Group two have a adequate communication of knowledge, skills, motivation and ability managing interaction. Some of the things he view is still lacking is the ability to communicate with new people who know, the ability to motivate others through communication (persuasive abilities), the attraction and motivation to communication.